Disharmony in The Regulation of Trading in Influence Within The Criminal Offense of Bribery and Its Impact on Governance - Amalia Syauket (Sociological Jurisprudence Journal, 2025)
In Indonesia, corruption has become akin to an advanced-stage cancer, difficult to cure and deeply entrenched. The severe consequences of corruption were a driving force behind the United Nations Convention Against Corruption (UNCAC) Summit held from December 9–11, 2003, in Merida, Mexico. This convention, ratified by 133 countries including Indonesia, became the first legally binding international anti-corruption instrument. However, the concept of trading in influence has yet to be formally adopted as a criminal offense under Indonesia’s Law on the Eradication of Corruption Crimes, despite being recognized as a distinct offense under Articles 12 and 18 of the UNCAC. The disharmony between trading in influence and the offense of bribery lies in several key aspects, although both are forms of corruption that must be addressed. This normative juridical research aims to identify the key aspects contributing to the disharmony in regulating trading in influence under bribery provisions, which in turn creates legal uncertainty. Furthermore, the study investigates the implications of this disharmony for governance. The academic analysis concludes that integrating trading in influence into the offense of bribery without clear distinction and careful consideration may lead to horizontal disharmony within the legal framework. Another consequence is that officials involved in trading in influence may be prosecuted under bribery provisions, thereby facing the risk of imprisonment and substantial fines. This regulatory gap also reveals a deficit in ethical integrity reflecting moral corruption among public officials which significantly undermines governance. Its direct consequences include declining public trust and the erosion of good governance practices. Ultimately, such corruption not only gradually dismantles state structures but also endangers the foundational interests of the nation.